Manga is Our World: The Use of Manga as Media in Teaching Writing Recount Text - Aini, Nufal; Indah, Rohmani Nur (English Education: Jurnal Tadris Bahasa Inggris, 2023)
Writing recount texts poses several challenges for students, including a lack of motivation, limited vocabulary, and difficulties understanding the narrative structure. Moreover, the inadequate availability of digital resources in some schools further restricts the teaching and learning process. To address these issues, this study explored the use of manga as a media tool in teaching writing recount texts. A qualitative descriptive research design was employed to describe and illustrate how manga can be effectively integrated into the teaching of writing recount texts in an XI-grade class at SMK Matsaratul Huda. The participants in this study were 22 students from the XI-grade class and an English language teacher. The findings reveal that using manga as a teaching medium for writing recount texts is a viable solution, particularly in the context of limited digital resources in schools. The manga approach enhanced students' motivation and fostered their ideation skills in writing recount texts. In conclusion, manga comics can be an effective medium for teaching writing recount texts, especially when faced with limited school digital resources. It increased student motivation and helped them better understand recount text structure and content.Writing recount texts poses several challenges for students, including a lack of motivation, limited vocabulary, and difficulties understanding the narrative structure. Moreover, the inadequate availability of digital resources in some schools further restricts the teaching and learning process. To address these issues, this study explored the use of manga as a media tool in teaching writing recount texts. A qualitative descriptive research design was employed to describe and illustrate how manga can be effectively integrated into the teaching of writing recount texts in an XI-grade class at SMK Matsaratul Huda. The participants in this study were 22 students from the XI-grade class and an English language teacher. The findings reveal that using manga as a teaching medium for writing recount texts is a viable solution, particularly in the context of limited digital resources in schools. The manga approach enhanced students' motivation and fostered their ideation skills in writing recount texts. In conclusion, manga comics can be an effective medium for teaching writing recount texts, especially when faced with limited school digital resources. It increased student motivation and helped them better understand recount text structure and content.